2009
DOI: 10.3354/meps07850
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of matrotrophy in the major classes of Bryozoa: transitions among reproductive patterns and their ecological background

Abstract: Bryozoa are unique among invertebrates in possessing placenta-like analogues and exhibiting extraembryonic nutrition in all high-level (class) taxa. Extant representatives of the classes Stenolaemata and Phylactolaemata are evidently all placental. Within the Gymnolaemata, placentalike systems have been known since the 1910s in a few species, but are herein reported to be widespread within this class. Placental forms include both viviparous species, in which embryonic development occurs within the maternal bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 65 publications
2
72
0
Order By: Relevance
“…It should also be noted that in contrast with the hypothesis of Silén (1945), our scenario requires fewer evolutionary steps and corresponds to accepted ideas on the evolution of bryozoan sexual reproduction (Boardman et al 1983;Taylor 1988;Reed 1991;Taylor 2004, 2005;Ostrovsky et al 2009;Ostrovsky 2009). …”
Section: Origin Of the Supraneural Coelomoporementioning
confidence: 67%
See 1 more Smart Citation
“…It should also be noted that in contrast with the hypothesis of Silén (1945), our scenario requires fewer evolutionary steps and corresponds to accepted ideas on the evolution of bryozoan sexual reproduction (Boardman et al 1983;Taylor 1988;Reed 1991;Taylor 2004, 2005;Ostrovsky et al 2009;Ostrovsky 2009). …”
Section: Origin Of the Supraneural Coelomoporementioning
confidence: 67%
“…However, the enlargement of the oocytes during the transition to the lecithotrophic larva in brooders (see Taylor 1988;Ostrovsky et al 2009) could make oviposition via the SNP more effective, and the ITO might be lost. On the other hand, the large oocyte size is obviously not an obstacle in some instances, since large oocytes are very elastic in gymnolaemate bryozoans.…”
Section: Secondary Loss Of the Itomentioning
confidence: 99%
“…This phylum is unique among invertebrates in that extraembryonic nutrition occurs in all major classes (Ostrovsky et al 2008(Ostrovsky et al , 2009a. Extraembryonic nutrition exists in at least 35 gymnolaemate (cheilostome plus ctenostome) genera among 26 families, and data from Harmer (1926), Cook (1985), and Kuklinski and Taylor (2006) suggest that there are likely to be more examples.…”
Section: Skeletal Ovicellsmentioning
confidence: 95%
“…Several studies have suggested that high maternal energy availability during gestation allows females to invest more energy in embryonic development. Such energy allocation is regarded as a selective advantage of matrotrophic reproduction (Trexler and DeAngelis 2003;Marsh-Matthews and Deaton 2006;Ostrovsky et al 2009;Itonaga et al 2012). If this is so, the relationship between food availability and the energetic costs of self-maintenance (i.e., net energy availability) during gestation may play a key role in the evolution of matrotrophic reproduction.…”
Section: Do Gravid Females Become Selfish? Female Allocation Of Energmentioning
confidence: 99%